Silicon negative electrode material and preparation method thereof

By using heat treatment, acid treatment and fluoride solution reaction steps in lithium-ion batteries, the problem of silicon negative electrode material due to volume expansion and natural SEI film overgrowth is solved, and a more stable battery is achieved Cycling performance and rate performance.

CN115312728BActive Publication Date: 2024-12-27WUHAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211012898.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-23
Publication Date
2024-12-27
Estimated Expiration
2042-08-23

AI Technical Summary

Technical Problem

The silicon negative electrode material is pulverized and structurally damaged due to volume expansion during the cycle of lithium-ion batteries, and the overgrowth of natural SEI film increases resistance, affecting battery performance. In the prior art, uneven fluoride coating leads to battery circulation performance and magnification. Unstable performance.

Method used

The reaction steps of heat treatment, acid treatment and fluoride solution are adopted to coat the SEI film in the liquid phase at room temperature to form a uniform and tight MgF2 artificial functional layer, improving the interface stability and electrochemical performance of the silicon negative electrode material.

Benefits of technology

Through uniform and tight SEI film coating, the structural stability of the silicon negative electrode material during the circulation process is improved, the cycle performance and rate performance of the battery are enhanced, the battery impedance is reduced, and the battery life is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003811609050000011
    Figure HDA0003811609050000011
  • Figure HDA0003811609050000012
    Figure HDA0003811609050000012
  • Figure HDA0003811609050000013
    Figure HDA0003811609050000013
Patent Text Reader

Abstract

The present invention relates to a silicon negative electrode material and a preparation method thereof. The preparation method of the present invention comprises the following steps: a heat treatment step S1: placing Mg2Si in a heat treatment device and heat treating it in a nitrogen atmosphere to generate a heat-treated product; an acid treatment step S2: placing the heat-treated product in an acid to react to generate an acid-treated product; a coating step S3: placing the acid-treated product in a fluoride solution at room temperature to react to obtain a porous silicon negative electrode material having an SEI film. The silicon negative electrode material obtained by the preparation method of the present invention has a SEI film that is more tightly combined with the silicon substrate and is more evenly coated, so that when the negative electrode material is used in a battery, its structure is more stable during the cycle process, thereby making the cycle stability and rate performance of the battery more stable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite material, in particular to a silicon negative electrode material and a preparation method thereof. Background Art

[0002] Graphite is the most commonly used negative electrode material in commercial lithium-ion batteries. However, its low specific capacity (372 mAh / g) can no longer meet people's daily needs.

[0003] In contrast, silicon has an extremely high theoretical capacity (4200mAh / g), but its huge volume expansion during battery cycling can lead to material pulverization and structural damage, and even cracking and falling off of the negative electrode material.

[0004] In addition, during the battery cycle, a natural SEI film will form on the surface of the silicon negative electrode material. The continuous cycle causes the film to become thicker and thicker, which in turn increases the resistance, is not conducive to the diffusion of ions, and the battery performance is also affected.

[0005] Artificial SEI film modified porous silicon negative electrode materials can improve the interface stability of the material and promote the transmission of lithium ions. At the same time, it can avoid direct contact between the silicon negative electrode material and the electrolyte to a certain extent, inhibit the excessive growth of the natural SEI film during the battery cycle, and reduce the battery impedance. This method can better improve the electrochemical performance of silicon negative electrode materials.

[0006] Chinese invention patent CN 109286014 A discloses a surface-modified silicon-carbon composite material and its preparation method and application. First, commercial raw materials containing silicon oxide are treated at high temperature and impurities are cleaned by acid washing to obtain silicon oxide; then, silicon oxide and fluoride are compounded by ball milling to obtain a silicon-based composite material.

[0007] However, the fluoride coating of the silicon negative electrode material of the invention is uneven. When it is used as a silicon negative electrode material in a battery, the battery cycle performance and rate performance are unstable.

[0008] Based on this, the present application proposes a silicon negative electrode material uniformly coated with a SEI film and a preparation method thereof to solve the above problems. Summary of the invention

[0009] The present invention provides a silicon negative electrode material and a preparation method thereof. The silicon negative electrode material obtained by the preparation method of the present invention has a SEI film that is more tightly combined with the silicon substrate and more evenly coated, so that when the negative electrode material is used in a battery, the technical problem of unstable battery cycle performance and rate performance caused by uneven and loose coating can be solved.

[0010] According to one aspect of the present invention, there is provided a method for preparing a silicon negative electrode material, comprising the following steps:

[0011] Heat treatment step S1: placing Mg2Si in a heat treatment device and heat treating it in a nitrogen atmosphere to generate a heat-treated product;

[0012] Acid treatment step S2: placing the heat-treated product in an acid for reaction to generate an acid-treated product;

[0013] Coating step S3: placing the acid-treated product in a fluoride solution for reaction at room temperature to obtain a porous silicon negative electrode material having a SEI film.

[0014] According to one embodiment of the present invention, the heat treatment in step S1 is: heating to a certain temperature at a rate of 1-20°C / min, and reacting at the temperature for 1 to 12 hours.

[0015] According to one embodiment of the present invention, the temperature in step S1 is raised to a certain temperature of 550-950°C.

[0016] According to one embodiment of the present invention, in step S2, the acid includes at least one of the following: hydrochloric acid, sulfuric acid, oxalic acid, and hydrofluoric acid.

[0017] According to one embodiment of the present invention, the concentration of hydrochloric acid in step S2 is 0.01-5 mol / L.

[0018] According to one embodiment of the present invention, the reaction time in step S2 is 1-12 hours.

[0019] According to one embodiment of the present invention, in step S3, the fluoride includes at least one of the following: NH4F, NaF, AlF3.

[0020] According to one embodiment of the present invention, the concentration of the NH4F solution in step S3 is 0.01-5 mol / L.

[0021] According to one embodiment of the present invention, the reaction time in step S3 is 1-12 hours.

[0022] According to another aspect of the present invention, the present invention also provides a silicon negative electrode material obtained by the preparation method of the present invention.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] In the method for preparing the silicon negative electrode of the present invention, since the coating step S3 is performed in the liquid phase, the coating is more uniform, and the coated SEI film is more tightly combined with the silicon substrate.

[0025] The silicon negative electrode material obtained by the preparation method of the present invention has a more uniform coating and the coated SEI film is more tightly combined with the silicon substrate, so that when it is used in a battery, its structure is more stable during the cycle process, thereby making the battery's cycle performance and rate performance more stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Prepared by Example 1 of the present invention Silicon anode material SEM images of

[0027] Figure 2 This is the XRD spectrum of the silicon negative electrode material prepared in Example 1 of the present invention;

[0028] Figure 3 This is a transmission electron microscope image of the silicon negative electrode material prepared in Example 1 of the present invention;

[0029] Figure 4 This is an electrochemical cycle data diagram of the silicon negative electrode material prepared in Example 1 of the present invention;

[0030] Figure 5 This is a scanning electron microscope image of the pure silicon negative electrode material prepared after being processed in steps S1 and S2 and then pickled and filtered;

[0031] Figure 6 The electrochemical cycle data of the pure silicon negative electrode material prepared after the treatment in steps S1 and S2 and acid washing and filtration. DETAILED DESCRIPTION

[0032] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] According to one aspect of the present invention, there is provided a method for preparing a silicon negative electrode material, comprising the following steps:

[0034] Heat treatment step S1: placing Mg2Si in a heat treatment device and heat treating it in a nitrogen atmosphere to generate a heat-treated product;

[0035] Acid treatment step S2: placing the heat-treated product in an acid for reaction to generate an acid-treated product;

[0036] Coating step S3: placing the acid-treated product in a fluoride solution for reaction at room temperature to obtain a porous silicon negative electrode material having a SEI film.

[0037] In the heat treatment step S1, the heat treatment device is selected from a tube furnace and a box furnace:

[0038] The magnesium in magnesium silicide has different reactivity with silicon in nitrogen. Magnesium will react with nitrogen to form magnesium nitride. Then, during the pickling process, magnesium nitride reacts with acid, and the solid particles form a uniform porous silicon skeleton. Due to the presence of magnesium ions in the solution, it can react with fluoride ions to form MgF2 precipitation, which is uniformly adsorbed on the surface of the porous silicon skeleton.

[0039] 3Mg2Si+2N2→3Si+2Mg3N2

[0040] Mg3N2+8H + →3Mg 2+ +2HH4 +

[0041] Mg 2+ +F - →MgF2

[0042] When the battery is charged and discharged for the first time, the electrolyte undergoes a reduction reaction on the surface of the negative electrode material, producing a large amount of organic or inorganic products that are deposited on the surface of the negative electrode to form a dense passivation film, namely the SEI film. + They can be freely embedded and removed through the SEI film. The continuous battery cycle causes the SEI film to become thicker and thicker, which in turn increases the resistance, hinders the diffusion of ions, and affects the battery performance.

[0043] According to the preparation method of silicon negative electrode material of the present invention, an artificial functional layer of MgF2, i.e., an artificial SEI film, is coated on the surface of the porous silicon negative electrode material. Since the coating step S3 is carried out in the liquid phase, the coating of the artificial SEI film is more uniform; and the coated SEI film is more tightly combined with the silicon substrate. The artificial SEI film can improve the interface stability of the silicon negative electrode material, avoid direct contact between the silicon negative electrode material and the electrolyte to a certain extent, inhibit the excessive growth of the natural SEI film during the battery cycle, reduce the battery impedance, and thus reduce the Li + loss and improve battery performance.

[0044] According to the method for preparing the silicon negative electrode material of the present invention, since the coating step S3 is carried out at room temperature, compared with the prior art which is carried out at extremely high temperature, it has the advantages of energy saving and environmental protection.

[0045] According to one embodiment of the present invention, the heat treatment in step S1 is: heating to a certain temperature at a rate of 1-20°C / min, and reacting at the temperature for 1 to 12 hours.

[0046] If the heating rate is less than 1°C / min, the time required to heat up to the target temperature will be too long. Once it is put into industrialization, it will increase the production cost of the entire industrialization process, which is not conducive to large-scale production. If the heating rate is greater than 20°C / min, the heating time can be shortened and the production cost can be reduced. However, the rapid heating in a short period of time will cause greater damage to the heat treatment equipment and increase safety hazards during production.

[0047] According to an embodiment of the present invention, the heating rate in step S1 is further preferably: 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20°C / min.

[0048] According to one embodiment of the present invention, the temperature in step S1 is raised to a certain temperature of 550-950°C.

[0049] According to an embodiment of the present invention, in step S1, within the heat treatment range of 550-950°C, Mg2Si is fully nitrided and the yield is high.

[0050] If the heat treatment temperature is lower than 550°C, the Mg2Si will not react fully during the nitridation process, and only a small amount of nitridation will occur, resulting in a low yield in the subsequent treatment process.

[0051] If the heat treatment temperature is higher than 950℃, although Mg2Si can be fully nitrided, the higher production temperature will lead to a sharp increase in production costs when put into production. And as the heat treatment temperature increases, the magnesium in magnesium silicide is easily lost in the form of gas, which reduces the uniformity of the porous silicon skeleton formed during the heat treatment reaction, which has an adverse effect on the electrochemical properties of the subsequent prepared materials.

[0052] According to the heat treatment method of the present invention, the heat treatment temperature in step S1 is further preferably: 550, 575, 600, 625, 650, 675, 700, 725, 750, 775, 800, 825, 850, 875, 900, 925, 950°C.

[0053] According to one embodiment of the present invention, in step S2, the acid includes at least one of the following: hydrochloric acid, sulfuric acid, oxalic acid, and hydrofluoric acid.

[0054] According to one embodiment of the present invention, the concentration of hydrochloric acid in step S2 is 0.01-5 mol / L.

[0055] According to an embodiment of the present invention, the concentration of hydrochloric acid is in the range of 0.01-5 mol / L, the sample reacts completely during the acid washing process, and the product purity is high.

[0056] If the concentration of the hydrochloric acid solution is higher than 5 mol / L, the sample will still undergo severe oxidation even under the condition of a short pickling time, reducing the purity of the product.

[0057] If the concentration of the hydrochloric acid solution is lower than 0.01 mol / L, the reaction during the sample pickling process is incomplete, residual magnesium nitride sample exists, and the final collected product has more impurities.

[0058] According to the acid treatment method of the present invention, the concentration of hydrochloric acid in step S2 is preferably: 0.01, 0.25, 0.5, 0.75, 1, 1.25, 1.5, 1.75, 2, 2.25, 2.5, 2.75, 3, 3.25, 3.5, 3.75, 4, 4.25, 4.5, 4.75, 5 mol / L.

[0059] According to one embodiment of the present invention, the reaction time in step S2 is 1-12 hours.

[0060] When the reaction time is 1-12h, the product purity can be maintained at 92%-98%

[0061] If the pickling time is too long, the sample will be severely oxidized.

[0062] If the pickling time is too short, the sample will not be pickled enough and the purity of the product will be significantly reduced.

[0063] According to one embodiment of the present invention, in step S3, the fluoride includes at least one of the following: NH4F, NaF, AlF3.

[0064] According to one embodiment of the present invention, the concentration of the NH4F solution in step S3 is 0.01-5 mol / L.

[0065] When the concentration of NH4F solution is 0.01-5mol / L, the thickness of SEI film formed on the surface of porous silicon sample is 5-15nm. When silicon negative electrode material is used in battery, it can ensure the optimal electrochemical performance of battery. -1 The discharge capacity range after 100 cycles at the current density is 1750-1800 mAh g -1 .

[0066] If the concentration of the NH4F solution is high, a large amount of MgF2 is generated on the surface of the porous silicon sample during the stirring process. The high MgF2 content increases the thickness of the surface SEI film, reduces the ionic conductivity of the product surface, and reduces the improvement effect of the electrochemical performance of the silicon negative electrode material obtained by the preparation method of the present application when used in a battery.

[0067] If the concentration of NH4F solution is low, MgF2 cannot form SEI film on the surface of porous silicon sample.

[0068] According to the coating method of the present invention, the concentration of the NH4F solution in step S3 is preferably: 0.01, 0.25, 0.5, 0.75, 1, 1.25, 1.5, 1.75, 2, 2.25, 2.5, 2.75, 3, 3.25, 3.5, 3.75, 4, 4.25, 4.5, 4.75, 5 mol / L.

[0069] According to one embodiment of the present invention, the reaction time in step S3 is 1-12 hours.

[0070] According to another aspect of the present invention, there is also provided a silicon negative electrode material obtained by the preparation method of the present invention.

[0071] The silicon negative electrode material obtained by the preparation method of the present invention has a more uniform coating and the coated SEI film is more tightly combined with the silicon substrate, so that when it is used in a battery, its structure is more stable during the cycle process, thereby making the battery's cycle performance and rate performance more stable.

[0072] According to the silicon negative electrode material prepared by the method of the present invention, there are a large number of porous channels inside the silicon, which can provide sufficient space for internal expansion. During the battery cycle discharge process, the volume expansion during the lithium ion embedding and extraction process can be effectively alleviated, so that the structural damage caused by the drastic volume expansion can be avoided to a large extent, thereby extending the battery life.

[0073] In order to explain the present invention in more detail, the present invention will be further described below in conjunction with specific embodiments and the accompanying drawings. It should be noted that the embodiments are only used to illustrate the present invention and will not limit the claims of the present invention.

[0074] Example 1

[0075] First, a heat treatment step S1 is performed: Mg2Si is placed in a tubular furnace and heat treated in a nitrogen atmosphere, heated from room temperature to 780°C at a heating rate of 5°C / min, kept warm for 6 hours, and then the furnace is cooled to room temperature to generate a heat-treated product; then an acid treatment step S2 is performed: after the heat-treated product is cooled to room temperature, the sample is ground with a mortar for 15 minutes, and the heat-treated product is placed in an acid for reaction, the acid is a hydrochloric acid solution, and the concentration of the hydrochloric acid solution is 1 mol / L to generate an acid-treated product; then a coating step S3 is performed: at room temperature, the acid-treated product is placed in a 1 mol / L ammonium fluoride solution for reaction for 3 hours, the reaction solution is filtered, and the filtered sample is dried in a freeze drying oven for 24 hours to obtain a porous silicon negative electrode material with a SEI film.

[0076] Example 2

[0077] Compared with Example 1, other conditions are exactly the same, except that the heat treatment temperature in step S1 is 550°C.

[0078] Example 3

[0079] Compared with Example 1, other conditions are exactly the same, except that the heat treatment temperature in step S3 is 950°C.

[0080] Example 4

[0081] The other conditions are exactly the same as those in Example 1, except that the concentration of hydrochloric acid in step S2 is 0.01 mol / L.

[0082] Example 5

[0083] The other conditions are exactly the same as those in Example 1, except that the concentration of hydrochloric acid in step S2 is 5 mol / L.

[0084] Example 6

[0085] Compared with Example 1, other conditions are exactly the same, except that the concentration of the ammonium fluoride solution in step S3 is 0.01 mol / L.

[0086] Example 7

[0087] Compared with Example 1, other conditions are exactly the same, except that the concentration of the ammonium fluoride solution in step S3 is 5 mol / L.

[0088] Comparative Example 1

[0089] A method for preparing a surface-modified silicon-carbon composite material comprises the following steps:

[0090] 1) calcining diatomite in air at 800° C. for 2 hours, washing the calcined product with 6 mol / L hydrochloric acid for 12 hours, and then washing with water for 5 times to obtain pure silicon oxide;

[0091] 2) Then the pure silicon oxide, magnesium powder and sodium chloride prepared in step 1) are mixed by ball milling, wherein the molar ratio of magnesium powder to pure silicon oxide is 2:1, and the weight ratio of sodium chloride to pure silicon oxide is 6:1; the ball milling speed is 180 r / min, and the ball milling time is 10 hours to obtain a mixture;

[0092] 3) placing the mixture prepared in step 2) in a magnetic boat, introducing argon gas, and performing a magnesium thermal reduction reaction at a reaction temperature of 800° C. for 10 hours, and cooling the obtained product to room temperature;

[0093] 4) washing the product of step 3) with 1 mol / L hydrochloric acid for 12 hours, then washing with water for 4 times, and then drying to obtain a nano-silicon composite material;

[0094] 5) Mixing the nano-silicon composite material prepared in step 4) with magnesium fluoride, and subjecting the mixture to oscillation ball milling, wherein the weight of the magnesium fluoride is 2% of the weight of the nano-silicon composite material, the frequency of the oscillation ball milling is 20 Hz, and the ball milling time is 3 hours, to obtain a silicon composite material with surface modified by magnesium fluoride.

[0095] Comparative Example 2

[0096] Compared with Example 1, other conditions are exactly the same, except that the heat treatment temperature in step S1 is 450°C.

[0097] Comparative Example 3

[0098] Compared with Example 1, other conditions are exactly the same, except that the heat treatment temperature in step S1 is 1050°C.

[0099] Comparative Example 4

[0100] The other conditions are exactly the same as those in Example 1, except that the concentration of hydrochloric acid in step S2 is 0.005 mol / L.

[0101] Comparative Example 5

[0102] Compared with Example 1, other conditions are exactly the same, except that the concentration of hydrochloric acid in step S2 is 6 mol / L.

[0103] Comparative Example 6

[0104] Compared with Example 1, other conditions are exactly the same, except that the concentration of the ammonium fluoride solution in step S3 is 0.005 mol / L.

[0105] Comparative Example 7

[0106] The other conditions are exactly the same as those in Example 1, except that the concentration of the ammonium fluoride solution in step S3 is 6 mol / L.

[0107] The silicon negative electrode material obtained in Example 1 was characterized, and the results were as follows:

[0108] Depend on Figure 1 From the scanning electron microscope image, it can be seen that the porous silicon composite material coated with MgF2 as the artificial functional layer prepared in this embodiment has a three-dimensional cross-linked porous structure, with a silicon core inside and MgF2 outside, and the coating of MgF2 makes its surface rough. Due to the low content of MgF2, the overall particle size of the silicon negative electrode material coated with MgF2 does not change.

[0109] Depend on Figure 2From the XRD diffraction pattern, it can be seen that the three strong peaks at 28.4°, 47.3° and 56.1° correspond to the three strong peaks of silicon (JCPDS No.27-1402), and the three strong peaks at 27.3°, 40.4°, and 53.5° correspond to the three strong peaks of MgF2 (JCPDS No.41-1443). The peak shapes are obvious and there is basically no impurity phase.

[0110] Depend on Figure 3 It can be seen from the transmission electron microscope image that the porous silicon composite material coated with MgF2 as an artificial functional layer prepared in this embodiment has a three-dimensional cross-linked porous structure. The internal porous structure provides a certain space for the internal expansion of silicon, which can alleviate the excessive volume expansion during the discharge process to a certain extent. In addition, MgF2 is coated on the surface of the porous silicon skeleton as an artificial functional layer, which increases the conductivity of its silicon matrix and exhibits excellent electrochemical properties.

[0111] Depend on Figure 4 From the electrochemical cycle data graph, it can be seen that the porous silicon composite material coated with MgF2 as an artificial functional layer prepared in this embodiment has a discharge specific capacity of 1758 mAh / g after 100 cycles at a current density of 1 A / g, showing excellent electrochemical performance.

[0112] Depend on Figure 5 From the scanning electron microscope image, it can be seen that the silicon prepared in this case has a porous structure and is three-dimensionally porous and connected.

[0113] Figure 6 From the electrochemical cycle data diagram of the pure silicon negative electrode material prepared after the treatment of steps S1 and S2 and then acid washing and filtration, it can be seen that the discharge specific capacity of the pure porous silicon material obtained through this process is 1301 mAh / g after 100 cycles at a current density of 1 A / g, which indicates that the cycle performance of the MgF2-coated porous silicon composite material is improved to a certain extent.

[0114] The mass before the first step of the reaction and the mass of the final sample were calculated by an electronic balance with a minimum weighing value of 0.1 mg, and the yields of Examples 1, 2, 3 and Comparative Examples 2-3 were calculated. The results are as follows:

[0115] Table 1-1

[0116] Example 1 Example 2 Example 3 Comparative Example 2 Comparative Example 3 Yield (%) 35 25 29 15 13

[0117] It can be seen from the above table that the heat treatment temperatures of Examples 1, 2 and 3 are in the range of 550-950°C. Compared with Comparative Examples 2-3, the Mg2Si is fully nitrided and the yield is high.

[0118] The purity of Examples 1, 4, 5 and Comparative Examples 4-5 was calculated, and the results were as follows:

[0119] Table 1-2

[0120] Example 1 Example 4 Example 5 Comparative Example 4 Comparative Example 5 purity(%) 98 98 92 92 91

[0121] It can be seen from the above table that the hydrochloric acid concentration in Example 1 is in the range of 0.01-5 mol / L. Compared with Comparative Examples 4-5, the sample pickling reaction is complete and the purity is high.

[0122] As can be seen from the above, in Examples 1, 6 and 7, the concentration of NH4F solution is in the range of 0.01-5 mol / L. Compared with Comparative Examples 6-7, according to the chemical formula of fluoride ions and magnesium ions, the amount of fluoride ion solution added is controlled so that the content of generated MgF2 is 1%-3%. The surface of the porous silicon sample was observed by transmission electron microscopy, and it was found that the thickness of the SEI film was 5-15 nm. When the silicon negative electrode material is used in a battery, the electrochemical performance of the battery can be optimized.

[0123] The above shows and describes the basic principles, main features and advantages of the present invention. Obviously, those skilled in the art can make various changes and modifications to the embodiments of the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a silicon negative electrode material, characterized in that: The following steps are involved: Heat treatment step S1: placing Mg2Si in a heat treatment device and heat treating it in a nitrogen atmosphere to generate a heat-treated product; Acid treatment step S2: placing the heat-treated product in an acid for reaction to generate an acid-treated product; Coating step S3: placing the acid-treated product in a fluoride solution for reaction at room temperature to obtain a porous silicon negative electrode material having a SEI film.

2. The preparation method according to claim 1, characterized in that: In step S1, the heat treatment is: heating to a certain temperature at a rate of 1-20°C / min, and reacting at the temperature for 1-12 hours.

3. The preparation method according to claim 2, characterized in that: The certain temperature is 550-950°C.

4. The preparation method according to claim 1, characterized in that: In step S2, the acid includes at least one of the following: hydrochloric acid, sulfuric acid, oxalic acid, and hydrofluoric acid.

5. The preparation method according to claim 4, characterized in that: The concentration of the hydrochloric acid is 0.01-5 mol / L.

6. The preparation method according to claim 1, characterized in that: In step S2, the reaction time is 1-12 hours.

7. The preparation method according to claim 1, characterized in that: In step S3, the fluoride includes at least one of the following: NH4F, NaF, AlF3.

8. The preparation method according to claim 7, characterized in that: In step S3, the concentration of the NH4F solution is 0.01-5 mol / L.

9. The preparation method according to claim 1, characterized in that: In step S3, the reaction time is 1-12 hours.

10. A silicon negative electrode material obtained according to any one of the preparation methods of claims 1-7.